Tingkat Adopsi Teknologi True Shallot Seed di Kecamatan Klambu, Kabupaten Grobogan - Pusdima Rahma Pratiwi; Siswanto Imam Santoso; Wiludjeng Roessali (Universitas Muhammadiyah Yogyakarta, 2018)
The productivity of shallot in Grobogan Regency is still low because the use of superior varieties is limited. The deployment of superior shallot seed technology that profitable is widely unknown to farmers. This research aims to analyze the adoption rate of true shallot seed (TSS) technology and the influence of internal and external factors of onion farmers on the adoption of TSS technology. The study was conducted in Klambu District, Grobogan Regency from July to August 2017 by interviewing 100 farmers who selected using multistage sampling. Data were analyzed using the descriptive method and logistic regression. The results showed that the adoption rate of TSS technology in Klambu District, Grobogan Regency was in a high category. Farmer’s age, land tenure status, cosmopolitan rate, requency of interaction with extension agent, and institutional support significantly influenced TSS technology adoption.